Sustainable substrate tin oxide/nanofibril cellulose/thermoplastic starch: dimensional stability and tensile properties - Azra N.A.; Atiqah A.; Jalar A.; Manar G.; Supian A.B.M.; Ilyas R.A. (Elsevier Editora Ltda, 2024)
Polymers used in thin films or substrates contribute to several environmental issues hence biodegradable materials should be used instead. In order to overcome this issue, the use of sustainable filler and reinforcements are needed to replace the existing synthetic materials. Nevertheless, the lower mechanical properties and higher water absorption could be hindered by incorporating Tin oxide (SnO) in nanofibril cellulose reinforced thermoplastic starch (NCF/TPS). In this study, different content of SnO (0, 1, 2, 3, 4, and 5 wt.%) with NCF/TPS nanocomposites was prepared by stir casting methods. The characterisation in terms of dimensional stability (density, water absorption, and thickness swelling) and tensile properties were studied. From the finding, it was found that the highest content of SnO leads to the lowest density, water absorption, and thickness swelling properties of SnO/NCF/TPS blend nanocomposites. Moreover, the incorporation of SnO at 4 wt.% shows good tensile properties than other formulations of SnO/NCF/TPS. 2023 The Author(s)